Kinfolk travel : slower ways to see the world - Burns, John Clifford (Artisan, 2021)
"Explore the art of mindful travel with Kinfolk, the pioneers in "slow living," their philosophy of simplicity, authenticity, intentionality and community. With nearly 450,000 copies in print, the Kinfolk series has applied this philosophy to entertaining (The Kinfolk Table), interior design (The Kinfolk Home), and living with nature (The Kinfolk Garden). Now they have turned their attention to "slow travel," offering readers a road map for planning trips that foster meaningful connections with local people and authentic experiences of local culture. Go museum hopping in Tasmania, or birdwatching in London. Explore the burgeoning fashion community in Dakar. Take a bicycle tour through Idaho, or a train trip from Oslo to Bergen. Drawing on the magazine's global community of writers and photographers, Kinfolk Travel takes readers to over 20 location across five continents, with travel tips from locals, stunning images, and thoughtful essays"--